Novel anthracene-based organic dyes as co-sensitizers of porphyrins for developing efficient dye-sensitized solar cells. (16th November 2021) - Tang, Yunyu; Yang, Guangxin; Lou, Xiaoyi; Li, Chengjie; Huang, Dongmei; Xie, Yongshu
Abstract : A high efficiency of 10.22% has been achieved through the cosensitization of anthracene-based organic dyes with a porphyrin dye. Abstract : To develop cosensitizers for fabricating dye-sensitized solar cells (DSSCs) based on porphyrin dyes, C2 and C3 have been synthesized using a diphenylamine donor, an anthracene based π-spacer and a benzoic acid acceptor on the basis of our previously reported cosensitizer C1 . Thus, two hexyloxy chains have been introduced in the diphenylamine donor to synthesize C2 with the purpose of extending the absorption wavelength range and suppressing the charge recombination, and C3 has been synthesized by introducing two bulky 2, 4-bis(hexyloxy)phenyl groups in the diphenylamine donor to effectively suppress dye aggregation and charge recombination between the injected electrons and the electrolyte. On this basis, DSSCs have been fabricated by using C1–C3 based on the cobalt electrolyte. As expected, an obviously higher J sc of 13.03 mA cm −2 has been obtained for C2 relative to that of 11.92 mA cm −2 obtained for C1 . As a result, C2 shows a slightly improved efficiency of 7.59%. On the other hand, the molecular structure of C3 has been further optimized with two bulky dihexyloxyphenyl units, and thus the suppressed interfacial back electron transfer improves the J sc to 13.23 mA cm −2 and the superior anti-aggregation ability enhances the V oc to 857 mV. Finally, the highest PCE value of 8.95% is achieved for C3 . On this basis, cosensitization with XW66 affords remarkable efficiencies of 9.06%, 9.89% and 10.22% for C1–C3, respectively. These results provide an effective approach for developing efficient cosensitizers for porphyrins by introducing suitable substituents into the donor unit.